Exploring the Openness of Global Research Landscapes Using Open Data: The COKI Open Access Dashboard - Napier, Kathryn; Montgomery, Lucy (My University, 2024)
Exploring the Openness of Global Research Landscapes Using Open Data: The COKI Open Access Dashboard - AfricArXiv Open Science Webinar Series 2024 Watch the recording here: https://africarxiv.pubpub.org/pub/8lnogfxn/
The Curtin Open Knowledge Initiative (COKI) seeks to be the world’s leading hub for analysis and evaluation of Open Knowledge in higher education. Founded in 2017 at Curtin University in Perth, Australia, the COKI project team collaborate with national and international partners to create fresh insights into Open Knowledge practices around the world. COKI has developed the world’s leading open knowledge data set, drawing together more than 12 trillion data elements, providing a comprehensive understanding of Open Knowledge practices and impact. The COKI project team has developed insights, analyses and tools which can enable universities to become Open Knowledge Institutions. The Curtin Open Knowledge Initiative (COKI) is a strategic initiative of the Research Office at Curtin, the Faculty of Humanities, School of Media, Creative Arts and Social Inquiry and the Curtin Institute for Data Science, with additional support from the Mellon Foundation and Arcadia, a charitable fund of Lisbet Rausing and Peter Baldwin.